European bank equity risk: 1995-2006 - Haq, Mamiza; Heaney, R. (2009)
We examine changes in bank equity risk following the formation of the Economic Monetary Union (EMU) in 1999. With the exception of Germany, we observe a decline in bank risk across euro-zone countries. Total risk decreased for 70% of the euro-zone banks in our sample with a statistically significant decrease in total risk observed for 51% of the sample. Similar results are found for idiosyncratic risk and systematic risk. These results are robust to financial crisis effects and test specification. Moreover, we find some evidence of a decrease in bank equity risk for a sample of neighbouring non-euro-zone European countries, consistent with the existence of some spill over effects. © 2008 Elsevier B.V. All rights reserved.